Career self-efficacy, organizational embeddedness, and inter-organizational mobility preparedness - Yap, Chui Yan; Poon, June M. L. (2009)
Drawing on the literature on contemporary careers, career transitions, and employee turnover, we examined the predictive effects of career self-efficacy and organizational embeddedness on inter-organizational mobility preparedness. We surveyed employees of a medium-sized company and analyzed the data (N = 173) using moderated multiple regression analysis. As expected, organizational embeddedness was negatively related to interorganizational mobility preparedness. In addition, organizational embeddedness moderated the relationship between career self-efficacy and inter-organizational mobility preparedness such that this relationship was stronger among employees who perceived low rather than high organizational embeddedness.